PROFESIONALISME GURU: KOPETENSI PEDAGOGIK DAN KOPETENSI SOSIAL - Janati, Salsabila; Aryati, Dwi; Mika; Swastini; Arif Wijaya, Hansein; Wulan Tersta, Friscilla (LPPM STAI Muhammadiyah Probolinggo, 2024)
The Importance of Education in National Progress: A Case Study of SMP Negeri 3 Bayung Lencir This article reviews the important role of education in national progress, with a focus on SMP Negeri 3 Bayung Lencir. As a key element in the education system, teachers play a central role in improving pedagogical and social competence. Pedagogical competence is improved through understanding the characteristics of students and developing semester lesson plans (SLPs). Meanwhile, social competence is enhanced through effective communication between teachers, students, and the community. The results of interviews show that teachers are making efforts to understand the characteristics of students and design SLPs to ensure that learning is structured. Communication between teachers is built through attitudes of tolerance and understanding, creating a pleasant learning environment. Participation in activities with the community is also a form of social competence improvement. These practices not only create an effective learning environment, but also improve competitiveness. However, it was found that there are challenges in social competence, namely teacher-student communication and students' lack of understanding. The steps taken to address these problems are by creating enjoyable learning, creating group discussions, and building communication with parents.